Edukasi dan Skrining Kasus Diabetes pada Pelajar di SMA Negeri 1 Palu - Afriani Kusumawati; Rumi, Amelia; Rudi Safaruddin; Arya Dibyo Adisaputra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Diabetes is a chronic disease that makes the body lose its ability to produce insulin or begin to use it less efficiently leading to high blood sugar. Without proper treatment, over time, this disease can lead to more serious health problems such as heart disease, vision loss, and kidney disease. Early detection and prevention are crucial in mitigating these risks. This study focuses on conducting an early screening for diabetes among high school students at SMA Negeri 1 Palu. Additionally, this activity aims to educate students at SMA Negeri 1 Palu on the importance of maintaining a healthy lifestyle by managing their sugar intake according to daily caloric needs. The program utilized an interactive educational approach, incorporating demonstration tools and discussions to enhance engagement and understanding. A total of 68 students participated in this initiative which was evaluated through a final assessment measuring knowledge improvement and awareness of diabetes prevention.